Self-rule : a cultural history of American democracy - Wiebe, Robert H. (Chicago : University of Chicago Press, 1995)
Self-Rule is a cultural history of democracy in the land of its origin. It is not a history of ideas on the one side or a detailed history of political behavior on the other. Rather, Wiebe examines the webbing of values and relations that gave democracy its meaning.
Machine derived contents note: Table of contents for Self-rule : a cultural history of American democracy / Robert H. Wiebe. -- Bibliographic record and links to related information available from the Library of Congress catalog -- Information from electronic data provided by the publisher. May be incomplete or contain other coding. -- Acknowledgments -- Introduction -- Part One: The American Exception 1820s-1890s -- 1. Democracy -- 2. The Barbarians -- 3. The People -- 4. In or Out -- Part Two: Metamorphosis 1890s-1920s -- 5. Sinking the Lower Class -- 6. Raising Hierarchies -- 7. Dissolving the People -- Part Three: Modern Democracy 1920s-1990s -- 8. The Individual -- 9. The State -- 10. Internal Wars -- Conclusion -- Notes -- Special Debts and Further Readings -- Index -- Library of Congress subject headings for this publication: United States Politics and government, Political culture United States History.
Includes bibliographical references and index.
Keywords: Political culture -- United States -- History; United States -- Politics and government; Politics -- History; United States